The strategies of development of innovative-technological potential of industrial enterprise forming - Hanna Blagevyth (Cхід, 2013)
Intercommunication is analyzed between going near development of innovative-technological potential of enterprise and management components in relation to his realization and conception of forming of strategy of development of innovative-technological potential of machine-building enterprise is offered.